Shrinking for Survival: Integrating Degrowth Principles into Texas Zoning Regulations - Alara Yücel; Pamela Durán-Díaz (Urban Science)
The degrowth movement is gradually gaining recognition within North American urban planning, but its influence and application remain limited. Most degrowth-oriented initiatives have remained at a small scale, mostly pertaining to communities and neighbourhoods. This study explores whether it is possible to incorporate degrowth principles into larger planning institutions and policies. The paper reviews existing studies on zoning policies and the degrowth movement, employing a qualitative research approach, and utilising secondary data analysis through document and critical discourse analysis. Through this exploration, this study aims to contribute to upscaling and institutionalising degrowth principles and to provide a clear outlook on the movement and its characteristics. Drawing on 32 key sources on zoning and degrowth, alongside two policy documents and a case study of Texas, this study applies coding, content analysis, and GIS mapping to explore the intersections of zoning regulations and degrowth principles in urban planning. The six key principles found to be essential to the degrowth movement—decoupling economics, fostering stronger communities, self-sufficiency, equity, political autonomy/collaboration, and ecological/environmental protection—were analysed in the context of the Texas municipal code for zoning to see whether current zoning ordinances follow the degrowth ideology. The findings reveal that while aspects of degrowth, such as affordable housing initiatives and environmental sensitivity, are present in Texas’ zoning regulations, these remain minimal and often constrained by the overarching focus on economic profitability. To integrate degrowth principles more effectively, significant reforms are required, including disengaging zoning ideologies from economic growth, fostering autonomy and self-sufficiency, and reimagining zoning practices to prioritise equity, ecology, and collective resource management.